Intracellular targeted co-delivery of shMDR1 and gefitinib with chitosan nanoparticles for overcoming multidrug resistance - Yu, Xiwei (Int J Nanomedicine, 2015)
Nowadays, multidrug resistance and side effects of drugs limit the effectiveness of chemotherapies in clinics. P-glycoprotein (P-gp) (MDR1), as a member of the ATP-binding cassette family, acts on transporting drugs into cell plasma across the membrane of cancer cells and leads to the occurrence of multidrug resistance, thus resulting in the failure of chemotherapy in cancer. The main aims of this research were to design a nanodelivery system for accomplishing the effective co-delivery of gene and antitumor drug and overcoming multidrug resistance effect. In this study, shMDR1 and gefitinib-encapsulating chitosan nanoparticles with sustained release, small particle size, and high encapsulation efficiency were prepared. The serum stability, protection from nuclease, and transfection efficiency of gene in vitro were investigated. The effects of co-delivery of shMDR1 and gefitinib in nanoparticles on reversing multidrug resistance were also evaluated by investigating the cytotoxicity, cellular uptake mechanism, and cell apoptosis on established gefitinib-resistant cells. The results demonstrated that chitosan nanoparticles entrapping gefitinib and shMDR1 had the potential to overcome the multidrug resistance and improve cancer treatment efficacy, especially toward resistant cells.